Multi-criteria Optimization of a Hybrid Renewable Energy for standalone electrification - et al., Chandarani Sutar (International Journal of Advanced Science and Technology, 2019)
In developing countries, designing a sustainable electrification system for remote places is very complex. Recently published research papers in the hybrid renewable field have not considered various factors such as technical, economic, environmental, and social (TEES), without which achievement of the goal of the sustainable energy system for rural places is not feasible. In the presented paper, a methodological framework based on decision analysis is designed with locally available renewable energy sources considering various TEES factors. Initially, suitable energy alternatives selected by considering different criteria with multiple scenarios for decision analysis. Further optimal combination of energy sources evaluated for different possibilities. The case study with real metrological data of a remote place in Himanchal Pradesh carried out, and the result shows that new methodology gave an optimized real-time system with multiple system combinations and configuration with the use of multitasking decisions algorithm and found very impactful on its TEES factor for the considered location.